Tidal volume optimization and heart rate response during stabilization of very preterm infants. Issue 2 (18th November 2022) - Cavigioli, Francesco; Bresesti, Ilia; Di Peri, Antonio; Cerritelli, Francesco; Gazzolo, Diego; Gavilanes, Antonio W. D.; Kramer, Boris; te Pas, Arjan; Lista, Gianluca
Abstract: Aim: To verify the added value of respiratory function monitor (RFM) to assess ventilation and the heart rate (HR) changes during stabilization of preterm infants. Methods: Preterm infants <32 weeks' gestation, bradycardic at birth and in need for positive pressure ventilation (PPV) were included. The first 15 min of stabilization was monitored with RFM. Three time points were identified according to HR values (T0 the start of mask PPV; T1 the HR rise >100 bpm; T2 the delivery of the last PPV). For each inflation, PIP, PEEP, MAP, expired tidal volume/kg (Vte/kg), and mean dynamic compliance (Cdyn) were analyzed. Results: PIP and MAP values were significantly higher at T1 (27.09 ± 5.37 and 17.47 ± 3.85 cmH2 O) and at T2 (24.7 ± 3.86 and 15.2 ± 3.78 cmH2 O) compared to T0 (24.05 ± 2.27 and 15.85 ± 2.77 cmH2 O). PEEP at T1 was significantly higher (6.27 ± 2.17 cmH2 O) compared to T2 (5.61 ± 1.50 cmH2 O). Vte/kg showed significantly lower T0 values (3.57 ± 2.14 ml/kg) compared to T1 (6.18 ± 2.51 ml/kg) and T2 (6.89 ± 2.40 ml/kg). There was a significant effect of time on Cdyn. Conclusions: A clear correspondence between HR rise and adequate Vte/kg during stabilization of very preterm infants was highlighted. RFM might be useful to tailor ventilation, following real‐time changes of lung compliance.